A biocontrol perspective on mycoviruses in fungal pathogen management - Galli, Matteo; Sede, Ana; Heinlein, Manfred; Kogel, Karl-Heinz; Justus Liebig University Giessen (My University, 2025)
Mycoviruses, viruses that infect fungi, have been identified across nearly every fungal taxon. Despite their widespread presence, the ecological effects of mycoviruses remain poorly understood. They can influence the biology of their hosts in various ways, including altering growth, reproduction, and pathogenicity. Their ability to induce either fungal hyper- or hypovirulence and thus regulate general fungal fitness by increasing fungal aggressiveness or, conversely, in extreme cases, converting harmful fungi into beneficial ones, has attracted increasing attention in recent years as a potential means of protecting plants from fungal diseases and pests. Increasing difficulties in controlling fungal diseases, pests and weeds with synthetic chemical pesticides, exacerbated by the emergence of resistance or tolerance to certain active ingredients, and stricter regulatory requirements due to environmental and health concerns, have stimulated interest in alternative approaches. In parallel with the introduction of double-stranded (ds)RNA-based products for crop protection and the fundamental knowledge generated in this field in recent years, the potential use of mycoviruses to control pathogenic fungi appears to be within reach. This review highlights recent advances in the field and emphasizes the potential of mycoviruses as biological control agents (BCAs), with the emphasis on the utilization of mycovirus-induced fungal hypovirulence to control fungi that cause plant diseases and mycovirus-induced fungal hypervirulence to protect plants from fungal hosts such insect pests or weeds.
Keywords: ddc:630